Dynamic model; the effects of eutrophication and sedimentation on the degradation of Coral Reefs in Spermonde Archipelago, Indonesia. Issue 1 (September 2020) - Faizal, A; Amri, K; Rani, C; Nessa, M N; Jompa, J
Abstract: Coral reef condition is influenced by many physical, biological, and anthropogenic processes. This research was designed to build a model between nutrient enrichment, sedimentation, and the abundance of herbivorous fish on macroalgae and coral reef coverage within the context of coral reef degradation. The research was conducted in the Spermonde Archipelago. The method used was the field survey method. The data were analyzed by using modeling instrument techniques. The results show that if there is no control over nutrient supply and sedimentation and efforts to increase the density of herbivorous fish, then the condition of coral reefs in Spermonde Archipelago is threatened with severe damage. The condition of coral reefs can be improved by decreasing nutrient supply and sedimentation of 6% each and increasing the herbivorous fish population by 5%.